2004
DOI: 10.1002/ceat.200401965
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dual Impeller‐Sparger Geometry on the Hydrodynamics and Mass Transfer in Stirred Vessels

Abstract: The understanding of the effect of impeller-sparger configurations on gas dispersion and mass transfer is very important to improve the performance of gas/liquid contactor systems. The influence of the impeller positions, the upper turbine diameter, the sparger ring diameter and its location in regard to the lower impeller on the power consumption, the volumetric masstransfer coefficient and the overall oxygen transfer efficiency were studied in a nonstandard curved bottomed reactor with an agitated system wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Experimental results for systems agitated with different impeller configurations show that the greatest values of the overall mass transfer coefficient were observed at low gas flow rates for spargers with a smaller ring diameter than the diameter of the impeller. On the other hand, at higher gas flow rates, the greatest k L a values are observed with spargers with large ring diameter [36]. In this work, in connection with the reactor operation conditions and the impellersparger geometry, a new model for the estimation of k L a values has also been proposed, with an average relative error of 8 %.…”
Section: Nishikawa Et Al As Well As With the Theoretical Equations mentioning
confidence: 96%
See 1 more Smart Citation
“…Experimental results for systems agitated with different impeller configurations show that the greatest values of the overall mass transfer coefficient were observed at low gas flow rates for spargers with a smaller ring diameter than the diameter of the impeller. On the other hand, at higher gas flow rates, the greatest k L a values are observed with spargers with large ring diameter [36]. In this work, in connection with the reactor operation conditions and the impellersparger geometry, a new model for the estimation of k L a values has also been proposed, with an average relative error of 8 %.…”
Section: Nishikawa Et Al As Well As With the Theoretical Equations mentioning
confidence: 96%
“…The following correlations are given in the literature for aqueous solutions of CMC, xanthan and polyacrylamide agitated by a stirrer arrangement of a propeller mixer and a helical ribbon stirrer with D/d = 1.14 [9,53]: [16,22,32,36,54]. Experimental results for systems agitated with different impeller configurations show that the greatest values of the overall mass transfer coefficient were observed at low gas flow rates for spargers with a smaller ring diameter than the diameter of the impeller.…”
Section: Nishikawa Et Al As Well As With the Theoretical Equations mentioning
confidence: 99%
“…For their rational design, the correlations of mass transfer coefficient and power dissipation have to be known for various combinations of the impellers. In the following papers, the power and mass transfer characteristics for various types and configurations of multi-impeller vessels can be found: Nocentini et al (1988Nocentini et al ( , 1993, Arjunwadkar et al (1998), Gogate and Pandit (1999), Vasconcelos et al (2000), Vilaca et al (2000), Bouaifi et al (2001), Gezork et al (2001), Moucha et al (2003), Garcia-Cortes et al (2004), Puthli et al (2005) and Fujasová et al (2007).…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, García‐Cortés et al reported a correlation where k L a was directly proportional to the impeller‐to‐vessel diameter (D/T) ratio raised to the power of 2.8. In the present study, simulations were consistent with the aforementioned findings in the sense that the larger impeller diameter produced higher k L a values.…”
Section: Resultsmentioning
confidence: 90%